Lattice strain gradient effects on hydrogen diffusion parameter calculations - Lewis, F.A.; Kandasamy, K.; Tong, X.Q. (Elsevier Science Ltd on behalf of the International Association for Hydrogen Energy, 2002)
With reference to proposals initially formulated by Gorsky (Phys. Z. Sowjetunion 8 (1935) 457), experimental evidence and theoretical arguments relating to stress/strain gradients resulting from migrations of hydrogen interstitials have been considered in studies with palladium and palladium alloys. In particular, Gorsky effect explanations have been proposed in interpretations of 'uphill diffusion effect' phenomena that have become substantially evidenced over the courses of studies of hydrogen diffusion behaviour.
Keywords: Gorsky effect; Stress/strain gradients; Uphill diffusion